Numerical analysis in rock cavern design - Yong, Yoon Chee. (2013)
Due to advancements in tunneling and supporting technology, underground space development has entered a new phase in Singapore. In recent years, new projects require an increased understanding of rock cavern response under various static and dynamic loads, such as the Jurong Rock Caverns for oil storage and Underground Science City beneath Kent Ridge Park, just to name a few.